THE ROLE OF INFORMATIZATION OF EDUCATION IN THE FORMATION OF FUTURE SPECIALISTS’ PROFESSIONAL COMPETENCE - Danylyuk, Serhiy (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Informatization of education as a process of introducing information technologies in various fields of modern educational system is studied in the paper. Four global trends, conditioned by broad computerization and informatization of pedagogical systems, are singled out in the paper. Four ideas and tendencies inherent in the field of education and influencing education informatization are also singled out in the paper. Four sub-goals of the global goal of informatization of education are singled out in the paper. Two strategic goals of the process of informatization of education are defined. Three levels of entering by an individual the world of computer science and computer engineering are distinguished